Modelling the relative abundance of the primary African vectors of malaria before and after the implementation of indoor, insecticide-based vector control - Sinka, ME; Golding, N; Massey, NC; Wiebe, A; Huang, Z; Hay, SI; Moyes, CL (BioMed Central, 2016)
Background Malaria remains a heavy burden across sub-Saharan Africa where transmission is maintained by some of the world’s most efficient vectors. Indoor insecticide-based control measures have significantly reduced transmission, yet elimination remains a distant target. Knowing the relative abundance of the primary vector species can provide transmission models with much needed information to guide targeted control measures. Moreover, understanding how existing interventions are impacting on these relative abundances highlights where alternative control (e.g., larval source management) is needed.